2012 IEEE 27th Conference on Computational Complexity 2012
DOI: 10.1109/ccc.2012.43
|View full text |Cite
|
Sign up to set email alerts
|

Reductions between Expansion Problems

Abstract: The Small-Set Expansion Hypothesis (Raghavendra, Steurer, STOC 2010) is a natural hardness assumption concerning the problem of approximating the edge expansion of small sets in graphs. This hardness assumption is closely connected to the Unique Games Conjecture (Khot, STOC 2002). In particular, the Small-Set Expansion Hypothesis implies the Unique Games Conjecture (Raghavendra, Steurer, STOC 2010).Our main result is that the Small-Set Expansion Hypothesis is in fact equivalent to a variant of the Unique Game… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(143 citation statements)
references
References 29 publications
4
139
0
Order By: Relevance
“…To the best of our knowledge, there is no hardness of approximation for MCLA in the literature. Its cousin MLA was recently proved SSE-hard to approximate within any constant factor (Raghavendra et al, 2012), and we observe that the same hardness applies to the MCLA problem.…”
Section: The Connection: Layout Problemsmentioning
confidence: 58%
See 3 more Smart Citations
“…To the best of our knowledge, there is no hardness of approximation for MCLA in the literature. Its cousin MLA was recently proved SSE-hard to approximate within any constant factor (Raghavendra et al, 2012), and we observe that the same hardness applies to the MCLA problem.…”
Section: The Connection: Layout Problemsmentioning
confidence: 58%
“…On the hardness side, our work builds upon the work by Raghavendra et al (2012), which showed that the SSE Conjecture implies superconstant hardness of approximation for MLA (and for c-balanced separator). The only other hardness of relative approximation that we are aware of for these problems is a result of the work of Ambühl et al (2007), showing that MLA does not have a PTAS unless NP has randomized subexponential time algorithms.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…For a constant ∈ (−1, 1), let N k, denote the infinite graph over R k where the weight of an edge (x, y) is the probability that two standard Gaussian random vectors X, Y with correlation 3 equal x and y respectively. The first k eigenvalues of N k, are at least 1 − (see [RST10b]). The following lemma bounds the expansion of small sets in N k, .…”
Section: Our Resultsmentioning
confidence: 99%